Reoperations after Total Correction Atrioventricular Communication - O. M. Dovgan; L. A. Shapoval; D. O. Dzyurman (Ukrainian Journal of Cardiovascular Surgery, 2016)
Certain number of patients after total correction of AVC require reoperation at a different times after surgery.24 patients after previous total AVC correction undergone reoperations. The average age of patients at the time of the second operation was 93,6±117,8 months (3 to 432 months). The average interval between radical correction and reoperation was 61,8±86,2 months (0.5 to 396 months). In 20 (83.3%) patients the main reason for reoperation had been mitral valve dysfunction. The second group consisted of 4 (16.7%) patients with subaortic stenosis.The common causes of mitral valve insufficiency: rupture of anterior leaflet, deterioration of the leaflet integrity at the patch fixation suture line and poor surgical technique during previous correction. In 19 (95%) patients with mitral insufficiency reconstructive surgery brought good results.Mostly papillary-chordal apparatus dysplasia of left atrioventricular valve led to subaortic stenosis development after correction of AVC among our patients. In this particular cases there was potential possibility for the need of valve replacement procedure.